Adaptation and cultural appropriation : literature, film, and the arts - Nicklas, Pascal; Lindner, Oliver (Spectrum Literaturwissenschaft, 2012)
"'Hamlet' by Olivier, Kaurismaki or Shepard and 'Pride and Prejudice' in its many adaptations show the virulence of these texts and the importance of aesthetic recycling for the formation of cultural identity and diversity. Adaptation has always been a standard literary and cultural strategy, and can be regarded as the dominant means of production in the cultural industries today. Focusing on a variety of aspects such as artistic strategies and genre, but also marketing and cultural politics, this volume takes a critical look at ways of adapting and appropriating cultural texts across epochs and cultures in literature, film and the arts"--Provided by publisher.